Estradiol enhances B cell humoral immune responses against genital herpes simplex virus type 2 in mice through an IL-17 dependant pathway - Mian, M. Firoz; Ghasemi, Ramtin; Bagri, Puja; McGrath, Joshua J. C.; Thayaparan, Danya; Niazy, Maysa; Snider, Denis P.; Kaushic, Charu (Frontiers in Immunology, 2025)
IntroductionEstradiol has been shown to enhance anti-viral immunity and protect against HSV-2 infection. Previously, we reported that intranasal immunization with attenuated HSV-2 (TK-) in the presence of estradiol (E2) showed enhanced Th17 responses that led to increased anti-viral Th1 immunity in HSV-2 post-challenge. Whether enhanced Th17 cells also lead to improved B cell antibody responses against HSV-2 challenge in immunized mice in the presence of E2 was not examined and is the focus of the current study.MethodsOvariectomized (OVX) C57BL/6 or IL-17 knockout (IL-17-/-) mice were implanted with 17β-estradiol (E2) or placebo pellets subcutaneously. Two weeks later, mice were immunized intranasally with a single dose of 104 pfu of TK- HSV-2 and 4- or 6-weeks later, blood sera and vaginal washes were collected to measure IgG total and subtypes by ELISA. Mice were challenged intravaginally with 104 pfu of WT HSV-2 4–6 weeks post-immunization, and vaginal washes were collected daily until euthanized at day 5 post-challenge to determine viral titers and protection. Mononuclear cells isolated from vaginal tract, spleen, nasal associated lymphoid tissue (NALT), cervical lymph nodes (cLN) and iliac lymph nodes (iLN) tissues were analyzed by flow cytometry for plasma and memory B cell phenotypes.ResultsE2-treated WT OVX immunized mice after intravaginal HSV-2 challenge showed significantly increased HSV-2-specific IgG2b and IgG2c antibodies in serum and vaginal secretions compared to placebo mice and enhanced B220-CD138+ IgG2c+ plasma cells within the nasal mucosa and vaginal tract 6-weeks after immunization. Furthermore, E2 treatment enhanced the subsets of CD19+ IgD- memory B cells 4-weeks post immunization within the iLN and spleen. Notably, E2-induced increased B cell antibody responses conferred greater protection from HSV-2 challenge compared to placebo mice as evidenced by 2–3 logs decreased viral titers in the vaginal tract and 20% mice with genital pathology compared to 80% in placebo group, indicating better protection in E2-treated mice. Importantly, E2-mediated enhanced plasma and B cell antibody responses observed in WT mice were abrogated in IL-17-/- mice that led to 2–3 logs higher viral titers that were equivalent in WT placebo- and IL-17-/- mice and no difference in protection.ConclusionThis study provides novel evidence that part of the E2-induced enhanced anti-viral response is mediated by increased B cell antibody responses that requires IL-17. Thus, E2 could be exploited in developing an effective mucosal vaccine driving B cells through intranasal immunization to elicit stronger HSV-2-specific antibody responses in the female genital tract.